IMPLEMENTASI ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN SEKOLAH DASAR: PELUANG DAN TANTANGAN BAGI GURU SDN MADANG MUSI RAWAS - Fitri, Yeyen; Iswatiningsih, Daroe (Penerbit Lafadz Jaya, 2025)
The development of Artificial Intelligence (AI) technology has had a major impact on the world of education, including at the elementary school level. This study aims to analyze the implementation of AI in learning at SDN Madang, Musi Rawas Regency, and to identify the opportunities and challenges faced by teachers in the process of adapting the technology. Using a qualitative approach and case study method, data were collected through in-depth interviews, observations, and documentation studies. The results of the study indicate that the implementation of AI at SDN Madang is still in its early stages, marked by the use of simple algorithm-based applications such as Google Classroom, Quizziz, and Kahoot. AI provides great opportunities to improve learning effectiveness, such as automatic feedback and analysis of student learning data. However, various challenges are still faced, including limited infrastructure, minimal digital literacy of teachers, and the absence of policies that support systemic AI integration. This study emphasizes the importance of strengthening teacher competence, improving technological infrastructure, and supporting inclusive policies to realize sustainable and equitable AI-based learning in elementary schools.